2016
DOI: 10.1038/ncomms12604
|View full text |Cite
|
Sign up to set email alerts
|

Actin dynamics provides membrane tension to merge fusing vesicles into the plasma membrane

Abstract: Vesicle fusion is executed via formation of an Ω-shaped structure (Ω-profile), followed by closure (kiss-and-run) or merging of the Ω-profile into the plasma membrane (full fusion). Although Ω-profile closure limits release but recycles vesicles economically, Ω-profile merging facilitates release but couples to classical endocytosis for recycling. Despite its crucial role in determining exocytosis/endocytosis modes, how Ω-profile merging is mediated is poorly understood in endocrine cells and neurons containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
180
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(195 citation statements)
references
References 67 publications
14
180
0
1
Order By: Relevance
“…Our result agrees with the fusion mechanisms found in simulations, where fusion is initiated by splaying of a single lipid and followed by lateral expansion of the fusion pore (32,45). This directly implies an important role of lateral tension for the progression from a stalk intermediate toward full fusion, in agreement with recent findings by Wen et al (46). Using Bell's theory and taking the force-dependent area increase into account, we found a reaction rate of τ In conclusion, we found that the main energy barrier toward fused lipid bilayers in the presence of SNAREs arises from a prestalk structure, in which the rate-limiting step is the displacement of solvent molecules from the interlamellar contact.…”
Section: Discussionsupporting
confidence: 93%
“…Our result agrees with the fusion mechanisms found in simulations, where fusion is initiated by splaying of a single lipid and followed by lateral expansion of the fusion pore (32,45). This directly implies an important role of lateral tension for the progression from a stalk intermediate toward full fusion, in agreement with recent findings by Wen et al (46). Using Bell's theory and taking the force-dependent area increase into account, we found a reaction rate of τ In conclusion, we found that the main energy barrier toward fused lipid bilayers in the presence of SNAREs arises from a prestalk structure, in which the rate-limiting step is the displacement of solvent molecules from the interlamellar contact.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with results in other systems, actin network disruption increases exocytosis in the hair cell ribbon synapse and actin may play a role in spatially organizing a sub fraction of synaptic vesicles around calcium channels (Guillet et al, 2016). In contrast, in chromaffin cells (Wen et al, 2016), even though F-actin dynamics mediate shrinking and merging of the membrane of LDCVs into the plasma membrane and actin coating was observed around some vesicles it only occurred after initiation of the shrinking and merging process. This indicates that actin coats may play different roles in the various secretory systems.…”
Section: Actomyosin Assembly On Vesicles Undergoing Fusion (Actin Coamentioning
confidence: 80%
“…However this would need to be confirmed using tension measurements in the presence of dynamin and/or myosin inhibitors. A recent study (Wen et al, 2016) found that dynamic assembly of cytoskeletal F-actin is necessary for shrinking and merging of the membrane of LDCVs into plasma membrane in chromaffin cells. F-actin imaging and tension measurements showed that this process is mediated by F-actin mediated plasma membrane tension.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane tension affects cell migration (Gauthier et al, 2011; Houk et al, 2012; Keren et al, 2008; Mueller et al, 2017), vesicle fusion and recycling (Boulant et al, 2011; Gauthier et al, 2011; Maritzen and Haucke, 2017; Masters et al, 2013; Shillcock and Lipowsky, 2005; Shin et al, 2018; Thottacherry et al, 2017; Wen et al, 2016), the cell cycle (Stewart et al, 2011), cell signaling (Basu et al, 2016; Groves and Kuriyan, 2010; Houk et al, 2012; Huse, 2017; Romer et al, 2007), and mechanosensation (He et al, 2018; Phillips et al, 2009; Ranade et al, 2015). However, there has been controversy over the speed and degree to which localized changes in membrane tension propagate in cells (Diz-Muñoz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%